THEORETICAL AND METHODOLOGICAL BASES OF STUDYING CONSUMER BEHAVIOR (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
In this paper theoretical and methodological bases of studying consumer behavior have been revealed, time analysis of consumer behavior has been done. These approaches of studying consumer behavior: economic, sociological and marketing have been analyzed. As a result, the strengths and weaknesses of each approach have been revealed. The implementation of complex and interdisciplinary approach is a must.
Keywords: consumer behavior; theoretical and methodological approaches; economic approach; economic man; sociological approach; consumer society; marketing approach